Computer Controlled Instrument for Measuring Magnetiresistance of GMR Film - Siritaratiwat, Dr.Apirat; Polrutanask, Prakornchai (Engineering and Applied Science Research, 2013)
This paper shows an instrument for measuring magneto-resitance of GMR films that the resistance is changed as a function of an applied magnetic field. This instrument is designed to be controlled by a computer for the convenience and the measurement reliability and so, the noise measurement is also concerned. A GMR film used for testing this instrument is a Fe/Cr multilayer. This is done by meeasring the resistance as the angular measurement and the bias current are changed. It is found that when a bias current is lower the percentage of GMR is higher. The coercivity, Hc, reaches its maximum value at the zero degree, or an easy axis, of film measurement. However, this instrument can measure other film properties as well.